Articulation between the Websites of the City Hall and the City Council of Tourism in Porto Seguro-BA / BR: The Importance of the Virtual City for Tourist Communication - Costa, Moabe Breno Ferreira (Journal of Tourism Management Research, 2019)
This study present a case study on the virtual tourist city, referring to the connection between the sites of the City of Porto Seguro-BA and the City Council of Tourism Development. It is a qualitative case study, following the trans-methodological rationality, using both retroductive and critical-dialectic methods. The methodological procedure analyzing both the structure and content of the websites. The characteristics and categories of attitudes defined by Levy (1999) served as parameters for analyzing the structure. Pertinent content was defined through questionnaires sent to high school and university students who live in Porto Seguro. This research has concluded that the articulation between the City of Porto Seguro-BA and the City Council of Tourism Development websites does not yet constitute an informational environment in keeping with the demands of tourism in cyberculture.